Handgrip strength assessment and its associated factors among hospitalized elderly in Klang Valley hospitals - Mohammed Yusufirashim, Khairunisar E Rashim; Omar, Noraida; Mohamad Shafie, Shazli Illyani; Nor'hisham, Siti Hazimah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Handgrip strength is a crucial biomarker of aging. Poor handgrip strength among hospitalized elderly increases the risk of health complications leading to a higher risk of hospital readmissions and mortality. This study aimed to determine handgrip strength among hospitalized elderly in Klang Valley hospitals alongside its associated factors. Methods: A total of 57 subjects were recruited for this study. Face-to-face interviews and physical assess- ments were conducted to obtain data on sociodemographic factors, medical background, anthropometry assess- ments and biochemical markers level. Dietary intake was obtained through two days of 24-hour dietary recall while tools such as Global Oral Health Assessment Index (GOHAI) and Mini Nutrition Assessment- Short Form (MNA-SF) were used to assess perception towards oral health and malnutrition risk, respectively. Reference value from the Asian Working Group of Sarcopenia (2014) was used to compare handgrip strength. Results: 94.7% of the subjects were found to have low handgrip strength with a mean value of 8.28 + 6.92 kg/force. Factors including age (r=- 0.370, p=0.005), educational level (r=0.471, p=<0.0005), perception towards oral health (r=0.370, p=0.005) and energy intake (r=0.367, p=0.005) were significantly associated with handgrip strength. Meanwhile, other variables were not significantly associated. Conclusion: The majority of the subjects had poor handgrip strength. Factors such as age, educational level, perception towards oral health and energy intake were significantly associated with hand- grip strength while the rest were non-significantly associated. Thus, more research and intervention strategies should be done to improve handgrip strength among hospitalized elderly to achieve a healthy aging nation.